Panel Data Regression Analysis of the Determinants of Educated Unemployment in East Java - Mudawamah, Haniatul; Amri, Muhtadin (Agregat: Jurnal Ekonomi dan Bisnis, 2024)
The primary goal of this research is to determine the relationship between the educated unemployment rate in East Java Province and several variables, including the minimum wage from 2018 to 2022, the labor force, and the human development index. This study included 190 secondary data samples in total, all of which came from the Central Bureau of Statistics' official website. For this investigation, the fixed effects panel data model (FEM) works well. This research demonstrates that: (1) the labor force and the educated unemployment rate do not correlate, or only partially correlate; (2) the educated unemployment rate is negatively impacted by the human development index; (3) there is a significant correlation between the educated unemployment rate and the minimum wage; and (4) in East Java, the minimum wage, the human development index, the labor force, and educated unemployment have a substantial correlation.